Supply Chain Collaboration from Supplier's Point of View: A Survey from European Manufacturing Industries - Puhtila, Lassi (My University, 2018)
This research aims to offer some insights what supplier organizations feel about supply chain collaboration. There is a lot of evidence in the previous literature about the benefits of supply chain collaboration. However, there are many potential barriers on why supply chain collaboration fails. In most of the previous literature, supply chain collaboration has been investigated mainly from the customer organization’s perspective. Because mutuality of benefits, risks, rewards and information sharing are the foundation of supply chain collaboration relationships, this research studies the phenomenon of supply chain collaboration from supplier organizations point of view. This research was a survey that was conducted by interviewing 67 different supplier organizations. These organizations were located in three different manufacturing sub-industries inside EU-28 countries. The opinions of these organizations about supply chain collaboration were first studied qualitatively by asking the respondents usage of different collaboration systems and their opinion of using these systems. After this, respondents’ opinion on four different barriers was asked by using Likert 5- point scale. This data was analysed later with the help of Kruskall-Wallis test, in order to gain understanding of the distributions of opinions between different departments where respondents were operating. Some respondents also shared their thoughts behind their selected answers, so these opinions are also introduced during the discussion part of the thesis. Because of this, it can be stated that this research used both qualitative and quantitative methods. In other words, this was a triangular research. The research results display that supplier organizations feel that their customers should be more willing to share risks and rewards with them, and this result was advocated among all the departments. Also, the current state of supply chain collaboration seems to be very complex with all the different systems that supplier organizations need to use with their clients. Generally, the respondents felt that these systems do not benefit them at all. At the end of the research some potential development ideas for solving this dilemma are offered.
Keywords: supply chain collaboration; manufacturing; information sharing; supply chain performance; supply chain management; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|